Tindakan Plagiarisme Pada Dunia Pendidikan: Studi Litratur Permasalahan Etika Pada Teknologi Informasi - Teddi Juliansyah (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2022)
Plagiarism in the field of education has become an increasingly concerning issue, particularly with the rapid advancement of information technology. This research presents a comprehensive literature review that examines the ethical problems arising from plagiarism in the context of information technology. It discusses the definition of plagiarism, various levels of plagiarism, the role of information technology in facilitating such misconduct, and its impact on academic integrity. In addition, this study explores the effectiveness of widely used plagiarism detection tools and the preventive strategies that educational institutions can adopt. Through this approach, the study provides an in-depth understanding of the dynamics of plagiarism in education and outlines efforts that can be taken to minimize such unethical practices. The conclusions derived from this review are expected to offer practical guidance for educational institutions, lecturers, and students in addressing ethical challenges related to information technology and fostering honorable academic practices.